Reference values (Z-score) of inlet and trabecular portion diameters of the right ventricle: First description in Spanish healthy children - Luisa García-Cuenllas Álvarez; Federico Gutiérrez-Larraya Aguado; Enrique Maroto Álvaro; Ana Rodríguez-López Domingo; Pedro Luis Sánchez Fernández; Luis García-Guereta Silva; Félix Lorente Toledano (Elsevier, 2020)
Introduction and objectives: Right ventricle (RV) measurements are crucial for certain congenital heart diseases and various cardiovascular conditions. Echocardiographic RV diameters are especially useful for its assessment. Paediatric echocardiographic data standardisation in normal subjects is complex, scarce, and heterogeneous. The aim of this study was to establish reliable and reproducible echocardiographic reference values (Z-score) of RV diameters in a healthy Spanish paediatric cohort. Methods: A multicentre study was conducted on 661 healthy subjects (age range 0-18 years, 43.5% female). Several regression models were tested to examine the relationship between RV diameters and biometric variables. Heteroscedasticity and residual associations (Shapiro-Wilk and Breusch-Pagan tests) and confounding factors (gender, age, inter/intraobserver agreement) were considered for an unbiased standardisation. Results: Structured Z-scores were computed for each RV diameter. Predicted mean value for each diameter was determined according to age, weight, height, and different body surface area. The Haycock formula provided the best fit for basal, midcavity, and longitudinal diameters (R2 0.81, 0.82, 0.9). Confounders were not significant, and therefore not included in final models (inter/intraobserver agreement > 0.9). Conclusions: This study reports reference values for echocardiographic RV diameters from a Spanish healthy paediatric cohort using a rigorous statistical design. These Z-scores partly cover a gap in current paediatric cardiology and represent a relevant diagnostic tool for clinical practice, as well as a useful guide to decision making at any paediatric stage. Resumen: Introducción y objetivos: La cuantificación del tamaño del ventrículo derecho (VD) es crucial en determinadas cardiopatías congénitas. Para su evaluación se recomiendan distintas técnicas de imagen, siendo más accesible la medición de diámetros ventriculares mediante ecocardiografía. En pediatría la normalización de parámetros ecocardiográficos es compleja, escasa y heterogénea. El objetivo de este estudio consistió en establecer Z-score de diámetros de VD fiables y reproducibles capaces de predecir valores de referencia en población pediátrica sana española. Métodos: Estudio multicéntrico prospectivo de 661 pacientes sanos (edades 0-18 años, 43.5% mujeres). Los diámetros ecocardiográficos del VD se relacionaron con variables biométricas mediante distintas ecuaciones de regresión. Para su estandarización se analizaron factores de confusión (sexo, edad y variabilidad inter/intraobservador), heterocedasticidad y residuos (test Saphiro-Wilk y Breusch-Pagan). Resultados: Se obtuvieron curvas de normalidad (Z-score) para cada diámetro del VD que permitieron predecir el valor medio de cada diámetro en función de la edad, peso, talla y distintas superficies corporales. La superficie corporal según fórmula de Haycock ofreció un excelente ajuste para los distintos diámetros basal, medial y longitudinal (R2 0.81, 0.82, 0.9). Los factores de confusión no aportaron cambios significativos, por lo que no fueron incluidos en los modelos finales (variabilidad inter e intraobservador, CCI > 0.9). Conclusiones: Se brindan valores de referencia de diámetros VD de población pediátrica sana. Las curvas de Z-score ofrecidas cubren una importante carencia en cardiología pediátrica y son aplicables a todos los grupos de edad para evaluar el tamaño del VD, de gran interés clínico en la práctica diaria.